KEBIJAKAN RESTRUKTURISASI UTANG MELALUI DEBT TO EQUITY SWAP - Wimba Respatia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
This research aim to obtain the understanding about debt restructuring to improve the efficiency and its productivity. An essential difference between these and the usual swapping of debt into equity is that the former allow a wider range of aplications. The firm’s owner have the option of choosing the sequence of restructuring negotiation with the creditors. The firm can combine the existing models, which is certainly with the agreement of the creditor and investor. This research has studied the choice of debt restructuring model carried out by PT X which is caused by the fact that the companies have difficulty paying their debts. Data collecting methods were conducted through literature study and field research from financial report of PT X. The result of this research indicate that PT X should choose debt for equity swap by converting their debt for equity swap that which giving lower cost of capital. By choosing debt for equity swap enable to change the liability profile from one to the other type, to create a more optimal capital structure debt equity and equity debt in what is called recapitalisation. Decision of converting their debt for equity swap will cause PT X be a mojority shareholder and increase the ability to compete with other aluminium company